IMPLEMENTASI KEBIJAKAN PEMERINTAH KABUPATEN SERANG NOMOR 3 TAHUN 2019 TENTANG PENGELOLAAN SAMPAH (STUDI KASUS DI DESA CIKANDE PERMAI) - Manurung, Zepanya; Bangsawan, Try Adhi; Saepudin, Eli Apud (Gapenas Publisher, 2025)
The issue of waste is a major problem faced in many locations, including Cikande Permai Village, located in Cikande District. With the increase in population and social activities, the volume of waste produced has also increased rapidly, while the available waste management system is still not functioning efficiently. The purpose of this study is to analyze the implementation of Policy No. 3 of 2019 concerning Waste Management based on the George C. Edward III model. A qualitative descriptive approach with data collection techniques through interviews, observation, and documentation is the technique or research method used in this study. The analysis was conducted based on Edward III's model, which consists of communication, resources, implementer disposition, and bureaucratic structure. This study shows that the implementation of the policy is not yet completely free from obstacles, such as a lack of formal communication, human resources, and facilities. Even so, community initiatives and local participation are beginning to grow. It is recommended that technical training, institutional strengthening, and cross-sector coordination be provided so that policy implementation can be more effective and sustainable.